Compensation for wrongful convictions : a comparative perspective - Jasiński, Wojciech; Kremens, Karolina (Routledge contemporary issues in criminal justice and procedure, 2023)
"This book presents a comprehensive comparative analysis of the substantive and procedural aspects of compensation for wrongful convictions among European countries and the USA, as well as the standard derived from the case law of the European Court of Human Rights. The collection draws comparative conclusions as to the similarities and differences between selected jurisdictions and assesses the effectiveness of the national compensation schemes. This enables the designing of an optimum model of compensation, offering accessibility and effectiveness for the victims of miscarriages of justice and being acceptable for jurisdictions based on common law, and civil law traditions, as well as inquisitorial and adversarial types of criminal process. Moreover, the discussion of the minimum European standard as established in the case law of the European Court of Human Rights enables us to identify how the Strasbourg Court can contribute to strengthening the compensation scheme. The book will be essential reading for students, academics and policymakers working in the areas of criminal law and procedure"--